On the outside, looking in: learning community languages and Scotland's 1 + 2 Language Strategy. Issue 3 (27th May 2021) - Hancock, Andy; Hancock, Jonathan
ABSTRACT: The Scottish Government's ambitious 1 + 2 Language Strategy has refocused attention on language education policy (LEP) and the provision for learning additional languages in Scottish schools. However, the maintenance of community languages continues to be the responsibility of minoritised parents and their complementary schools. This article reports on a national survey of complementary school providers in order to gain insights into their perspectives of community language learning during the implementation of the 1 + 2 Language Strategy . Data are analysed using a Critical Language Policy (CLP) lens and reveal a complex picture of provision for teaching and learning community languages, outside of mainstream schools, and an untapped resource for language planning and valuing the linguistic diversity of Scotland. The article concludes with a discussion to inform future developments of the 1 + 2 Language Strategy, among which is greater engagement with language communities and a more nuanced planning approach to language learning for contemporary societies.